Działalność pastora Jamesa Lawsona w Nashville 1958-1960 („nonviolent workshop”, sit-ins) – studium przypadku walki o zmiany społeczno-polityczne - Marta Baranowska (Ksiegarnia Akademicka Publishing, 2019)
In Nashville in 1958 Reverend James Lawson and Reverend Kelly Miller Smith (NCLC) started organising „nonviolent workshop”. Lawson began teaching and train local residents in the techniques of the Gandhi philosophy of direct nonviolent protest. On February 14 and 28, 1960, African American students launched their first full-scale sit-ins. Throughout the spring, students conducted numerous sit-ins and boycott. They suffered physical abuse, arrests, but held to the concept of Christian nonviolence. On April 19, after bombing damaged the home of Z. Alexander Looby (defense counsel for the students), thousand of black and some white Americans marched to Nashville’s City Hall. On May 10, 1960, Nashville became the first major city to begin desegregating its public facilities. The Nashville movement had been planned over several months, and served as a model for future demonstrations against segregation.